PERLINDUNGAN HUKUM TERHADAP ANAK DALAM SENGKETA PERKAWINAN DAN PERCERAIAN: ANALISIS YURIDIS DALAM SISTEM HUKUM INDONESIA - Dafa Ferdiansyah; Fitria Agustin (PT. Hasba Edukasi Mandiri, 2026)
This study aims to conduct a juridical analysis of the legal protection of children in marriage and divorce disputes within the Indonesian legal system. Children are considered vulnerable parties in domestic conflicts and are often the most affected, particularly in matters related to custody, financial support, education, and the fulfillment of fundamental rights. Although Indonesian positive law has provided regulations concerning child protection after divorce through various statutory provisions, its implementation in practice still faces significant challenges, especially regarding the enforcement of court decisions and the level of compliance by disputing parties. This research employs a normative juridical method with statutory and conceptual approaches. The legal materials used consist of primary legal sources, including laws and regulations on marriage and child protection, as well as secondary legal materials such as legal literature, scholarly journals, and academic doctrines. The analysis is conducted qualitatively to examine the alignment between legal norms and their practical implementation in society. The findings indicate that although there are relatively comprehensive regulations governing child protection in divorce disputes, a gap still exists between legal norms and their implementation. The main issues lie in weak law enforcement, inadequate supervision of court decisions, and low legal awareness among the parties involved. Therefore, it is necessary to strengthen and integrate legal protection mechanisms more effectively to ensure the realization of the principle of the best interest of the child in every marriage and divorce dispute process in Indonesia.